Analyzing the Determinants of Students’ Reading Interest in the CANDIL Digital Library Application - Aqila, Nabila Imtiyazul; Fikri, Aceng Munir Akmalul Fikri; Nurahmi, Dwi Sukma; Hildansyah, Irdan (Jurnal Tadwin, 2025)
This study aims to explore how students' psychological needs, namely autonomy, competence, and relatedness, can be met or hindered in using the CANDIL (Maca Dina Digital Library) application, using the Self-Determination Theory (SDT) approach. The method used is qualitative with data collection techniques in the form of observation, interviews, and questionnaires. The results showed that the autonomy aspect tends to be fulfilled even though it is limited by the variety of collections, the competence aspect is still constrained by features that -are confusing for some students who use the CANDIL. It can also be seen that the relatedness aspect is still not maximized due to the lack of interaction space between users. In conclusion, although the CANDIL application has provided easy access and some support for reading interest for students using the CANDIL, the fulfillment of the three psychological needs has not been maximized. This shows that strategies to increase interest in reading in the digital era do not simply rely on adequate technology, but must also consider psychological or motivational factors that can affect the experience and increase interest in reading for users.